A study of anomalous events in CMS-HF PMTs - Halu, Arda. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
The Forward Hadronic (HF) calorimeter of the CMS detector will measure the hadronic jets as well as determine the missing transverse energy generally attributed to new physics phenomena. HF is a quartz ber calorimeter in which the Cerenkov light generated by charged particles is collected by conventional photomultiplier tubes (PMT). In the HF test beam of 2004, events with unusually high energies with respect to the incoming beam energy were seen. These abnormal events were later con rmed in the 2007 test beam study. In this thesis, anomalous events are studied in various aspects, with more emphasis on the comparison of their electromagnetic (EM) and hadronic (HAD) channel signals. EM/HAD and HAD/EM energy ratio histograms are plotted for several pion and muon test runs with di erent beam momenta. Incident tower ratio histograms in the typical energy range display a clear peak, justifying the existence of a correlation while histograms of abnormally high energy events for the sum of all other towers do not exhibit such a relation. This observation might help us infer that these anomalous events, which most probably result from particles striking PMT windows directly instead of passing through bers to reach them, are of no experimental signi cance and may be tagged as \unreal" events to be discarded.
Keywords: Hadrons.; Calorimeters.; Particles (Nuclear physics)